Food traceability system from governmental, corporate, and consumer perspectives in the European Union and China: A comparative review. (May 2020) - Qian, Jianping; Ruiz-Garcia, Luis; Fan, Beilei; Robla Villalba, Jose Ignacio; McCarthy, Ultan; Zhang, Baohui; Yu, Qiangyi; Wu, Wenbin
Abstract: Background: Food safety has garnered much worldwide attention recently for reasons that are, unfortunately, not always positive. Traceability system (TS) is designed to assure safe and good quality food, while reducing the costs of food recalls. It should encompass all stakeholders, including governments, companies, and consumers, each of whom has an important role in the implementation and guardianship of such systems. The EU and China are amongst the main players implementing TS and are constantly exploring new opportunities and monitoring challenges for TS in a time of shifting consumer demands and rapid new technology innovation. Scope and approach: This article states development stages from TS 1.0 to 3.0. and reviews TS development in a number of key countries and regions. Comparisons between the EU and China are drawn in terms of government, corporate, and consumer involvement in traceability. Key findings and conclusions: A functional TS, while providing bi-directional communication between trading partners, must meet the laws and regulations where it operates. A functional system must also consider consumer value and perception, which varies with geography. There are a variety of promising technologies available on the market today to modernize TS, including artificial intelligence (AI) and blockchain. A key finding of this research is that both the EU and China have developed significant trade links in recent years which will certainly positively impact both economies. Key to underpinning the sustainability of these trade links will be the adoption of common TS to prevent negative associations. Highlights: Present a comprehensive analysis framework from government, company and customer perspectives. Comparative review between the EU and China. Outline the trend of traceability development with the AI and blockchain technologies. Highlight the strategic technological and consumer-based requirements for global scale traceability systems. Provide multi-stakeholder perspectives and inputs of traceability.